2016
DOI: 10.1016/j.mayocp.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function After the First Kidney Stone Event

Abstract: Objective To determine if there is a persistent decline in kidney function after the first kidney stone event. Patient and Methods Incident symptomatic stone formers and age- and sex-matched controls underwent 2 study visits 90 days apart to assess kidney function, complete a survey, and have their medical records reviewed. Kidney function was compared between stone formers and controls adjusting for clinical, blood, and urine risk factors. Results There were 384 stone formers and 457 controls. At visit 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
0
19
0
5
Order By: Relevance
“…Indeed, other recent publications demonstrated a correlation between dpucMGP and kidney function, leading to the hypotheses that kidney disease may lead to vitamin K deficiency or conversely, that vitamin K deficiency is a risk factor of kidney damage [24,25]. As shown previously, stone formers have an increased cystatin C levels that may be associated with the risk of chronic kidney disease [12]. While no study has directly reported an association between vitamin K status and urolithiasis, it is well-known that higher vegetables intake decrease the risk of urolithiasis [26].…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Indeed, other recent publications demonstrated a correlation between dpucMGP and kidney function, leading to the hypotheses that kidney disease may lead to vitamin K deficiency or conversely, that vitamin K deficiency is a risk factor of kidney damage [24,25]. As shown previously, stone formers have an increased cystatin C levels that may be associated with the risk of chronic kidney disease [12]. While no study has directly reported an association between vitamin K status and urolithiasis, it is well-known that higher vegetables intake decrease the risk of urolithiasis [26].…”
mentioning
confidence: 76%
“…The lower limit of quantification was 300 pmol/L and the upper reference range 521 pmol/L (CI 513-550 pmol/L). The other laboratory parameters were previously assessed at the Mayo Clinic in Minnesota (USA) as previously described [12]. Serum creatinine was measured by standardized isotope dilution mass spectrometry traceable enzymatic assay (Roche), and serum cystatin C by particle-enhanced turbidimetric assay (Gentian AS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil ini tidak berubah setelah dilakukan followup 3 bulan oleh peneliti. 4 Bergsland dkk dari University of Chicago menemukan bahwa marker protein urin dapat membedakan individu dengan risiko stone former dan non stone former. Mereka melakukan analisa elektroforesis protein urin dan berkesimpulan bahwa inter-a-trypsin inhibitor (ITI), prothrombin fragment 1 (PF1), CD59, dan calgranulin B (calB) berhubungan dengan angka kejadian dan rekurensi batu saluran kemih.…”
Section: Pendahuluanunclassified
“…The prevalence of kidney stone disease is ~10% worldwide (Scales, Smith, Hanley, & Saigal, ; Wang et al, ) and is progressively increasing owing to various factors, including metabolic abnormalities caused by diet and environment (Morgan & Pearle, ). Increased incidences of acute or chronic kidney injury (Sigurjonsdottir, Runolfsdottir, Indridason, Palsson, & Edvardsson, ) resulting from renal dysfunction owing to kidney stones could jeopardize public health (Haley et al, ). In addition, nephrolithiasis has been recognized as a systemic disorder (Shadman & Bastani, ), which is associated with the development of diverse cardiovascular diseases (Alexander et al, ).…”
Section: Introductionmentioning
confidence: 99%